Examining the Relations Between Self-Regulation and Achievement in Third-Grade Students. (March 2017) - Day, Stephanie L.; Connor, Carol McDonald
Children with stronger self-regulation skills generally demonstrate greater overall success in school both academically and socially. However, there are few valid and reliable measures of self-regulation in middle elementary school. Such a measure could help identify whether a child is truly having difficulties. Thus, the Remembering Rules and Regulation Picture Task (RRRP) was developed. The aim of this study was to develop scoring systems for the RRRP and then to examine the associations between RRRP and independent measures of self-regulation and academic achievement in mathematics and reading. Children ( N = 282) from 34 third-grade classrooms in Florida participated in this study. Results revealed that the RRRP captured three constructs: working memory, attentional flexibility, and inhibitory control. Hierarchical linear modeling (HLM) demonstrated that the RRRP was significantly and positively associated with other measures of self-regulation. The RRRP was significantly and positively associated with mathematics and reading as well. The RRRP appears to be a promising measure of children's self-regulation skills.